2020
DOI: 10.3329/bjb.v49i3.49641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators on quality flower and seed production of marigold (Tagetes erecta L.)

Abstract: Effects of different growth regulators and their application time on production of quality flower and seed production of marigold (Tagetes erecta L.) were investigated. Experimental factors include nine foliar applications of growth regulators viz., Control (no application), two doses each of GA3, salicylic acid, benzyl adenine, cycocel, and two application times viz., (i) application at 25 DAT, (ii) application at 50 DAT. Results suggest that foliar spray of 250 ppm gibberellic acid enhanced growth, and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Our results are in agreement with those obtained by, Mazrou (2017), on chamomile plants, Attia and Moftah (2003) on borage plants, Khalil et al, (2010); Abd El-Salam (2014) and Marzok et al (2017) on sweet basil plants, Choudhary et al (2016) on African marigold plants, Niri et al (2016) on marigold plants, Abdul-Basit et al (2018);Abbas et al (2019) and Kumar et al (2019) on Tagetes sp. regarding salicylic acid treatments.…”
Section: Photosynthetic Pigmentssupporting
confidence: 92%
“…Our results are in agreement with those obtained by, Mazrou (2017), on chamomile plants, Attia and Moftah (2003) on borage plants, Khalil et al, (2010); Abd El-Salam (2014) and Marzok et al (2017) on sweet basil plants, Choudhary et al (2016) on African marigold plants, Niri et al (2016) on marigold plants, Abdul-Basit et al (2018);Abbas et al (2019) and Kumar et al (2019) on Tagetes sp. regarding salicylic acid treatments.…”
Section: Photosynthetic Pigmentssupporting
confidence: 92%
“…Due to increased reproductive efficiency and photosynthesis in the restructured plant type, more shoots were produced at an early stage of growth, giving them enough time to accumulate carbohydrates for proper flower bud differentiation, which ultimately increased the yield per plant and per square metre. Kumar et al [6], Alhajhoj et al [8]. These results are confirmed from those reported by Kumar et al [10] who recorded a substantial increase in number of flowers when plants were treated with GA3 at 150 ppm in carnation, was also observed by Nandre et al [17], China aster, Baghele et al [14] in Rose, Sharma and Joshi [18] in China aster.…”
Section: Resultssupporting
confidence: 74%
“…By promoting cell division and elongation, foliar treatment of GA3 may have affected the stem lengthening and canopy expansion. Additionally, under the impact of GA3, which retains swelling force against with the softening of cell wall and increases plant height, growth may be accelerated by osmotic uptake of water and nutrients [6]. These findings are in conformity with Sajid et al [7], Alhajhoj et al [8] and Girisha et al [9] in daisy A similar trend was observed regarding the number of leaves parameter where maximum number of leaves (203.67) was observed when GA3 @ 200 ppm was applied followed by that of 175ppm (200.33) concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of GA 3 on plant growth is more distinct when the application takes place at the correct stage (vegetative) of plant development [ 34 ]. In the current studies, significantly higher growth parameters in the two-time spray might be due to the supply of GA 3 at the juvenile stage that causes rapid growth in the initial period as compared to the application at triple time spray when the plant has almost attained its maturity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%